Focusing on social behaviors: Improving the perceived warmth of sharks in an aquarium setting - Neves, Joao (2023)
Sharks are commonly depicted as intentionally dangerous predators and are considered a threat by the general public, limiting support for and success of global shark conservation. Following the SCM framework, this study aimed at testing the effect of information on the social lives of sharks alone or paired with circumstantial humor on the participants’ perceived warmth of sharks before visiting an aquarium. The present study took place in a naturalistic setting, allowing testing of the variables in a pseudo-real-world environment where results can objectively help in the implementation of strategies on the ground. A total sample of 303 visitors participated in this study, where three conditions (control: 100; social information: 102; social information with humor: 101) were tested. Results showed that, although mild, it was possible to affect the warmth dimension of the shark’s stereotype, most likely due to the presence of information about the social lives of sharks. This information slightly leveraged the perceived warmth dimension, although still far from the less threatening stereotype as aimed. Results also highlight the possible importance of using videos within the strategic communication and education approaches in aquariums in order to be most effective in challenging the shark stereotype. Limitations and future research ideas are explored.